Efficient isopropanol-butanol-ethanol (IBE) fermentation by a gene-modified solventogenic Clostridium species under the co-utilization of Fe(III) and butyrate. (April 2023) - Zhang, Feifei; Zhang, Kan; Zhang, Zhiqian; Chen, Hai-Qi; Chen, Xiao-Wei; Xian, Xing-You; Wu, Yi-Rui
Graphical abstract: Highlights: The addition of Fe 3+ can strengthen the sugar uptake and shorten the fermentation. The ABE yield and productivity were enhanced via the optimal co-utilization system. The introduction of adh enables to efficiently eliminate the acetone production. The solvent production and acid re-assimilation were improved from strain WK:adh. A maximum of 25.46 g/L total IBE biosolvents was finally achieved. Abstract: To elevate the efficiency of acetone-butanol-ethanol (ABE) fermentation by the wild-type strain WK, an optimal co-utilization system (20 mM Fe 3+ and 5 g/L butyrate) was established to bring about a 22.22% increment in the yield of ABE mixtures with a significantly enhanced productivity (0.32 g/L/h). With the heterologous introduction of the secondary alcohol dehydrogenase encoded gene ( adh ), more than 95% of acetone was eliminated to convert 4.5 g/L isopropanol with corresponding increased butanol and ethanol production by 21.08% and 65.45% in the modified strain WK::adh. Under the optimal condition, strain WK::adh was capable of producing a total of 25.46 g/L IBE biosolvents with an enhanced productivity of 0.35 g/L/h by 45.83% over the original conditions. This work for the first time successfully established a synergetic system of co-utilizing Fe(III) and butyrate to demonstrate a feasible and efficient manner for generating the value-added biofuels through the metabolically engineered solventogenic clostridial strain.